The absence of the problem of the thing in itself in Hegel’s philosophy in the face of Hegel’s understanding of truth - Jochlik, Artur Jerzy (Folia Philosophica, 2019)
The article presents a Hegelian view of Kant’s thing in itself in regard to Hegel’s understanding of truth. In it, I designate eight key fragments of The Phenomenology of Spirit, around which the analysis of the issue takes place. As a result, the boundaries have been defined in which Hegel wants to pursue his deliberations. Hegel does not want to think about what is independent of the cognizing subject, claiming that it does not concern us, philosophers because it is the task of religion. The truth for Hegel is what realizes itself among us so that it is fully available to us.